Recent development of the nonlinear optical active material system - Kim, N (WILEY-V C H VERLAG GMBH, 1996)
New nonlinear optical active materials have been highlighted to apply them to practical applications since about two decades ago. During this period, a number of materials have been developed and studied in academic and industry field. Particularly, the second-order nonlinear optical properties are facile to approach in the laboratory. We can consider the possibility of the device application by investigating the macroscopic second-order nonlinear optical properties using the second harmonic generation and linear electro-optic study. Nowadays, the absolute value of the nonlinear optical coefficient of organic material overcame the value of conventional inorganic materials due to quick research progress. Therefore, the new organic materials systems showed some promising motives to fabricate the optical device.
Keywords: 2ND